Knowledge and Awareness Regarding Stock Market Participation among Undergraduate Dental Students - Nagaraju, Dr. Sanka; Pratap, Dr. K. V. N. R.; Padma, Dr. T. Madhavi; Kumar, Dr. Srujan; Singh, Dr. Surbhit; Chandra, Dr. Myneni Jaideep (International Journal Of Drug Research And Dental Science, 2025)
Aim: To compare dental scholars’ research to find out how well-informed and involved students are in the stock market. Students who have some background in the stock market are more probable to have a good grasp of personal finance and to make prudent financial choices on the road, according to the research. Students might get a feeling of agency and mastery over their own financial destiny by investing in the stock market. We can, however, state that students should not engage in the stock market without first fully comprehending the dangers of doing so and then proceed with extreme care and a focus on the long term. According to the research, college students would be well-served by programs that teach them about money and the stock market.